Sanksi Tindak Pidana Terorisme Dalam Undang-undang Nomor 5 Tahun 2018 Tentang Pemberantasan Tindak Pidana Terorisme dan Hukum Pidana Islam - Sudiro, Sudiro; Gani, Ruslan Abd; Hidayati, Rahmi; Halim, Abdul (Journal of Health Education Law Information and Humanities, 2025)
The crime of terrorism is a crime that receives very serious attention in terms of its handling. This is proven by the creation of a complete explanation of the sanctions for perpetrators of criminal acts of terrorism both in Islamic law and in Positive Law. This thesis discusses the Sanctions for Criminal Acts of Terrorism in the Republic of Indonesia Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism and Islamic Criminal Law. The method used in this research is library research. Research refers to sources including: the Quran, Hadith, Laws, Books, Theses and opinions or statements of Legal Experts. The Crime of Terrorism in Islamic Criminal Law is an act that violates sharia whose sanctions are equated with jarimah hirābah. Meanwhile, in Positive Law, sanctions for criminal acts of terrorism are regulated in Law Number 5 of 2018, the sanctions of which are in the form of imprisonment of at least 4 years and a maximum of 20 years and the death penalty.